2012
DOI: 10.1103/physreve.86.020302
|View full text |Cite
|
Sign up to set email alerts
|

Time dependence and density inversion in simulations of vertically oscillated granular layers

Abstract: We study a layer of grains atop a plate which oscillates sinusoidally in the direction of gravity, using three-dimensional, time-dependent numerical solutions of continuum equations to Navier-Stokes order as well as hard-sphere molecular dynamics simulations. For high accelerational amplitudes of the plate, the layer exhibits a steady-state "density inversion" in which a high-density portion of the layer is supported by a lower-density portion. At low accelerational amplitudes, the layer exhibits oscillatory t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Similar results were obtained before by e.g. Bougie, Policht & Pearce (2012). There, however, mild driving conditions are considered which lead to maximum volume fractions way below 0.3.…”
Section: Bouncing Bed Testsupporting
confidence: 87%
“…Similar results were obtained before by e.g. Bougie, Policht & Pearce (2012). There, however, mild driving conditions are considered which lead to maximum volume fractions way below 0.3.…”
Section: Bouncing Bed Testsupporting
confidence: 87%
“…To isolate the possible effects of the two-dimensionality of our experiments on height-oscillations, additional experiments (not shown) were conducted in a quasi-2D box (of width of about 5 particle diameter, W/d = 5.5, and length L/d = 100) with a shallow granular layer (F = h 0 /d = 6); increasing the shaking intensity from 30 to 40, however, we found that the Leidenfrost state remains a "period-1" wave, implying that the LS is synchronized with the shaking frequency even in a quasi-2D vibro-fluidized bed. Simulations in a 2D-box and/or additional experiments may help to resolve the disagreement between the above simulations [46,49] and our experiments about the synchronous time-dependence of the Leidenfrost state.…”
Section: B Height Oscillations In Granular Leidenfrost Statementioning
confidence: 73%
“…(It may be noted that the low-and high-Γ regimes in simulations of Ref. [49] correspond to the same shaking strength (S = Γ(A/d) = constant) but having small-and large-A/d, respectively.) To isolate the possible effects of the two-dimensionality of our experiments on height-oscillations, additional experiments (not shown) were conducted in a quasi-2D box (of width of about 5 particle diameter, W/d = 5.5, and length L/d = 100) with a shallow granular layer (F = h 0 /d = 6); increasing the shaking intensity from 30 to 40, however, we found that the Leidenfrost state remains a "period-1" wave, implying that the LS is synchronized with the shaking frequency even in a quasi-2D vibro-fluidized bed.…”
Section: B Height Oscillations In Granular Leidenfrost Statementioning
confidence: 95%
See 1 more Smart Citation
“…If a granular Leidenfrost effect truly exists during the emplacement of RAs, a relatively dispersed basal layer should be generated at the base of RAs 41,42 . Does this truly exist?…”
Section: Ra Ow Regimementioning
confidence: 99%